Quality of life and functional status of patients treated with venovenous extracorporeal membrane oxygenation at 6 months - Kanji, Hussein D.; Chouldechova, Alexandra; Harris-Fox, Samantha; Ronco, Juan J.; O'dea, Ephraim; Harvey, Chris; Shuster, Constantin; Thiara, Sonny; Peek, Giles J. (Journal of critical care, 2021)
Quality of life (QoL) outcomes of patients treated with extracorporeal membrane oxygenation (ECMO) for acute respiratory distress syndrome (ARDS) have been conflicting. This study reports on QoL outcomes for a broad group of ARDS patients managed with up-to-date treatment modalities. We prospectively recruited patients at a quaternary hospital in the United Kingdom from 2013 to 2015 who were treated with ECMO for ARDS. We evaluated their pulmonary function and QoL at 6-months after admission using three QoL instruments: EuroQoL 5D (EQ-5), HADS, and PTSS-14. Forty-three patients included in the analysis had near-normal pulmonary function at 6 months. HADS showed moderate-to-severe anxiety and depression in 32% and 11% of patients, respectively. PTSS-14 showed 29% had signs of post-traumatic stress disorder. EQ-5D showed that 67% of patients had difficulty returning to usual activities, 74% suffered some pain, none reported severe problems and 77% were able to return to work. No clinical or demographic variables were associated with poor 6-month QoL. Patients with ARDS treated with ECMO generally had good QoL outcomes, similar to outcomes reported for patients managed without ECMO. With respect to QoL, VV-EMCO represents a valid treatment modality for patients with refractory ARDS. •ARDS survivors treated with ECMO experience some anxiety, depression and post-traumatic stress 6 months after discharge•Most survivors of ECMO support for ARDS were able to return to work at 6-months post hospital discharge•Most survivors of ECMO support for ARDS had near normal pulmonary function at 6-months post hospital discharge•With respect to quality of life, veno-venous ECMO support is a valid treatment modality for refractory ARDS